Efficacy of therapeutic plasma exchange in HELLP syndrome: A single-center experience (Annals of Medical Research, 2025)
Aim: The objective of this study is to investigate the clinical efficacy of therapeutic plasma exchange in HELLP (Hemolysis, Elevated Liver Enzyme, Low Platelet) syndrome and its contribution to renal failure, which is an independent risk factor for maternal mortality.Materials and Methods: From 2019 to 2024, 20 patients diagnosed with HELLP syndrome who underwent therapeutic plasma exchange (TPE) were included. We evaluated the patients' pre- and post-procedure values to determine the efficacy of the procedure.Results: The median age of patients was 30 (19-38) years, and the median number of days of TPE was 6 days (3-14). There was a statistically significant increase in hemoglobin and platelet values and a statistically significant decrease in lactate dehydrogenase, total bilirubin, direct bilirubin, aspartate aminotransferase, alanine aminotransferase, urea, and creatinine values. The number of TPE sessions, length of stay in hospital, and the length of intensive care unit stay were significantly higher in hemodialysis patients.Conclusion: TPE is an effective treatment modality for both clinical improvement and prevention of permanent renal failure in patients with persistent postpartum hemolysis who are followed for HELLP syndrome.
Keywords: HELLP syndrome; Therapeutic plasma exchange; Renal failure